2020
DOI: 10.1038/d41586-020-01813-8
|View full text |Cite
|
Sign up to set email alerts
|

Cool metric for lithium-ion batteries could spur progress

Abstract: Lithium-ion batteries get hot, and it is hard to keep them cool. Industry has paid too little attention to this problem for the past decade. The focus has been elsewhere: on cutting costs and on boosting the amount of energy a single cell in a battery can store (energy density). This strategy has, for example, increased the longevity and capabilities of mobile phones. Future applications, such as electric vehicles and smart grids, need thousands of cells in a battery pack. These are prone to overheating.Manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 5 publications
(10 reference statements)
0
32
0
Order By: Relevance
“…With respect to the cell-level limitations, one important consideration is the geometry of commercially available lithium foil (minimum thickness of 50 μm and maximum width of 10 cm [58] ), which limits the overall cell geometry and the optimization of the ratio between the active and inactive component mass. Consequently, nickel tabs have to be adapted for these electrode geometries and for each application (high power vs high energy, see Section 2.3), as these tabs usually play a key role in cell cooling [59] as well as transfer current. Another limitation is the pouch cell as a cell type, as some applications prefer cylindrical cells with a stainless steel casing.…”
Section: Limitationsmentioning
confidence: 99%
“…With respect to the cell-level limitations, one important consideration is the geometry of commercially available lithium foil (minimum thickness of 50 μm and maximum width of 10 cm [58] ), which limits the overall cell geometry and the optimization of the ratio between the active and inactive component mass. Consequently, nickel tabs have to be adapted for these electrode geometries and for each application (high power vs high energy, see Section 2.3), as these tabs usually play a key role in cell cooling [59] as well as transfer current. Another limitation is the pouch cell as a cell type, as some applications prefer cylindrical cells with a stainless steel casing.…”
Section: Limitationsmentioning
confidence: 99%
“…If the battery becomes too hot, there is a possibility of a thermal runaway reaction, which could lead to a battery fire. Good recent reviews of (fast) battery charging and cooling methods for batteries can be found in references [31,32].…”
Section: Thermal Fluids For Control Of Battery Temperaturementioning
confidence: 99%
“…As discussed in reference [32], some electric vehicles (such as the Nissan Leaf) are air cooled-they simply rely on the flow of air through the battery cells to cool the battery (some cars rely on the motion of the vehicle for airflow through the battery, whereas others actively pump the external air so that it flows faster through the battery cells). However, this is not entirely satisfactory as the air ambient temperature can vary widely.…”
Section: Thermal Fluids For Control Of Battery Temperaturementioning
confidence: 99%
“…If the battery becomes too hot, there is a possibility of a thermal runaway reaction, which could lead to a battery fire. Good recent reviews of (fast) battery charging, and cooling methods for batteries can be found in references [26] and [27].…”
Section: Thermal Fluids For Control Of Battery Temperaturementioning
confidence: 99%